2014
DOI: 10.1186/cc13852
|View full text |Cite
|
Sign up to set email alerts
|

Body cell mass evaluation in critically ill patients: killing two birds with one stone

Abstract: Body cell mass (BCM) is the metabolically active cell mass involved in O2 consumption, CO2 production and energy expenditure. BCM measurement has been suggested as a tool for the evaluation of nutritional status. Since BCM is closely related to energy expenditure, it could also represent a good reference value for the calculation of nutrient needs. In a recent issue of Critical Care, Ismael and colleagues used bioelectrical impedance analysis parameters and anthropometric variables to evaluate BCM in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…This study found a high percentage of moderate-to-high burnout among intensivists, similar to intensivists from other countries (7,9,10) and to other Brazilian studies (12,13,15,16) showing that the percentages of considerable burnout were near to or even greater than 50%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study found a high percentage of moderate-to-high burnout among intensivists, similar to intensivists from other countries (7,9,10) and to other Brazilian studies (12,13,15,16) showing that the percentages of considerable burnout were near to or even greater than 50%.…”
Section: Discussionsupporting
confidence: 89%
“…(5-8) Intensivists may have high burnout levels because of the stressful and demanding work associated with critical patient care. (6,9) …”
Section: Introductionmentioning
confidence: 99%
“…There was an approximately 10% higher level of burnout and 17% higher level of dissatisfaction as compared to the general population in this particular study [4]. A high level of emotional exhaustion, depersonalization, and low personal accomplishments were reported among the nurses and respiratory therapists working in the intensive care unit (ICU) in the US [3]. Though the burnout in the medical field seems to be a universal phenomenon, it is not well documented in the literature.…”
Section: Introductionmentioning
confidence: 95%
“…Burnout has been studied among practicing doctors in many parts of the world including the USA [3-4], European countries [5-6], and Latin America [7], while very few studies are being reported from India [8-9]. In a study conducted in the USA in 2012, 7288 physicians completed a survey in which 45.8% of the physicians showed at least one symptom of burnout.…”
Section: Introductionmentioning
confidence: 99%
“…[12] In India, situations are very diverse and different depending upon the hospitals location, ownership, admission policies, etc.…”
mentioning
confidence: 99%